Implikasi Konsep Utilitarianisme dalam Penegakan Hukum Tindak Pidana Narkotika: Kajian Putusan Pengadilan Negeri Yogyakarta Nomor 389/Pid.Sus/2015/PN.Yyk - Shinta Rhukmi B. (Universitas Slamet Riyadi, 2019)
The criminal justice system is a significant element in efforts to eradicate narcotics crime. Drug users should get severe criminal sanctions, considering that victims of narcotics abuse in Indonesia are increasing from year to year. However, in terms of law enforcement the Supreme Court through the Decision of the Yogyakarta District Court Number 389 / Pid.Sus / 2015 / PN Yyk only contains formulations that are not supported by scientific theories, even the decision does not include informatio on the period of detention or the provisions of Article 197 paragraph ( 1) letter h of Law Number 8 of 1981. This type of research is normative legal research. Normative legal research prioritizes literature. The results of the study indicate that the binding force of Article 197 paragraph (1) of Law Number 8 of 1981 is mandatory, imperative and limited in the judge's decision, which aims to provide values of justice and protection of human rights for the parties. The consequences of these provisions if not fulfilled in the judge's decision are the verdict null and void.